"Voice calling in the desert street" - Some captivated remarks on Petr Rezek's book - Činátlová, Blanka (Bohemica Olomucensia, 2012)
The author concentrates on the question of "being with work of art" with regards to thoughts in Petr Rezek's book Tělo, věc a skutečnost v umění šedesátých a sedmdesátých let, e. g. how to understand the art, what is the core of critic's point of view on work of art, what is the rule of spectator's or reader's enchantment with the work of art or what are the relations of contemporary art to the European art tradition.